Predictors of Success of Ablation Procedures in Patients with Non-Structural Premature Ventricular Contraction at Adam Malik Hospital - Asepty, M. Rizky Priyanka; Lubis, Anggia Chairuddin; Mukhtar, Zulfikli (CoinReads Media Prima, 2024)
Introduction: According to previous research, catheter ablation reduces premature ventricular contractions and improves heart function more than pharmaceutical treatment. Gender, age, LVEF, and premature ventricular contraction origin are utilized to predict ablation success. This study aims to determine the predictors of success of the ablation procedure in patients with non-structural premature ventricular contractions. Method: This study is an observational analytical study with a retrospective cohort design to assess predictors of success of the ablation procedure in patients with non-structural premature ventricular contractions at H Adam Malik General Hospital, Medan. Results: There were 55 research subjects and the majority of patients were female, 37 people (67.3%) with an average age of 47.2 ± 12.39 years. There was a significant relationship between premature ventricular contractions originating from the RVOT and the success of the ablation procedure (p < 0.001), but there were no significant differences in ablation therapy based on gender, age and LVEF (p > 0.05). Conclusion: The origin of premature ventricular contraction from the RVOT is a predictor of the success of the ablation procedure in patients with non-structural premature ventricular contact.